(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study proves the importance of determining the composition and quantitative ratio of the vaginal microbiota in bacterial vaginosis for the selection of differentiated therapy. Two-stage therapy of bacterial vaginosis, selected taking into account the molecular biological variants of vaginal dysbiosis, had a persistent treatment effect in 87.3% of cases. The additional use of probiotics of the oligosaccharide group as an anti-relapse therapy enhances the colonization of lactobacilli and ensures the stability of the vaginal biotope in 95.4% of cases.